Improved H2SO4‐catalyzed alkylation reaction in a rotating packed bed reactor by adding additives. (6th March 2022) - Tian, Yuntao; Mei, Sijing; Zhang, Liang‐Liang; Chu, Guang‐Wen; Sun, Baochang; Fisher, Adrian C.; Luo, Yong; Zou, Hai‐Kui
Abstract: The isobutane/butene alkylation process catalyzed by an acid solution is widely used to obtain high octane number gasoline components. However, limited by the mass transfer and mixing of the acid solution and the hydrocarbon liquid–liquid system, the product performance needs to be improved. Here, the alkylation reaction was strengthened by combining the chemical regulation of the reactant system and process intensification. Three homologs of sulphates and two hydrophilic surfactants were used as additives to regulate the properties of the acid solution, and the effect of different additives on isobutane/butene alkylation was investigated in a rotating packed bed. The Hammett acidity and solubility of isobutane in acid solutions with different additives were measured, and their synergistic effects on alkylation performance were explored. Under relatively mild conditions (the reaction at 8°C and an isobutane/butene ratio of 30:1), an excellent alkylate with a research octane number of approximately 99 was obtained, showing good industrial application prospects.